IMPLEMENTASI KEWAJIBAN NOTARIS DALAM PENGENAAN PAJAK PERTAMBAHAN NILAI (PPn) - Israwati Akib (Cross-border, 2021)
The purpose of this study was to identify and analyze the implementation of notary obligations in the imposition of value added tax (VAT). This study uses empirical normative research methods. Data obtained through field research conducted through observation, interviews and questionnaires. Primary data and secondary data were processed using qualitative analysis. The results show that the implementation of VAT collection as a Notary obligation has not run effectively because in its implementation there are still Notaries who do not issue Tax invoices in collecting VAT for the provision of their services even though the responsibilities as a Taxable Entrepreneur have been carried out in accordance with the applicable rules, but in the process the administration of deposits and their calculations are still much assisted by tax consultants so that many notaries do not understand the administrative process.